2008
DOI: 10.1111/j.1467-9507.2007.00440.x
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Differential Treatment and Child Adjustment: A Multi‐informant Approach

Abstract: The study aimed to replicate previous links with children's adjustment as well as using children's reports of maternal differential treatment (MDT) to test whether difference scores or favouritism scores demonstrate stronger links with child outcome. Finally, it tested for a unique prediction of children's adjustment from distinct aspects and informants of MDT. The sample consisted of 173 working-and middle-class English families with two children aged four to eight years. Mothers provided reports of the mothe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
59
1
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(66 citation statements)
references
References 33 publications
4
59
1
2
Order By: Relevance
“…Since parental support remains important during adolescence, it is likely that sibling comparison processes are enhanced (White, 2001;Siennick, 2013). The notion that children are more likely to compare themselves to a same-gender sibling is consistent with findings from the current study as well as past research (e.g., Coldwell et al, 2008). It was evident that some sibling participant's experienced parental differential treatment, which contributed to a more negative sport experience, increased competitiveness between siblings, and jealousy.…”
Section: Understanding Parent Influencesupporting
confidence: 80%
See 1 more Smart Citation
“…Since parental support remains important during adolescence, it is likely that sibling comparison processes are enhanced (White, 2001;Siennick, 2013). The notion that children are more likely to compare themselves to a same-gender sibling is consistent with findings from the current study as well as past research (e.g., Coldwell et al, 2008). It was evident that some sibling participant's experienced parental differential treatment, which contributed to a more negative sport experience, increased competitiveness between siblings, and jealousy.…”
Section: Understanding Parent Influencesupporting
confidence: 80%
“…Parents' unequal treatment could undermine sibling relationship quality, as siblings are each other's best point of comparison for parental treatment. In fact, parental differential treatment is most pronounced in same-gender dyads (Coldwell, Pike, & Dunn, 2008). Since parental support remains important during adolescence, it is likely that sibling comparison processes are enhanced (White, 2001;Siennick, 2013).…”
Section: Understanding Parent Influencementioning
confidence: 99%
“…In most cases PDT is operationalized as a simple difference score (parenting towards one child subtracted from parenting towards his/her sibling), however PDT has also been measured by asking directly about experiences of favoritism. For example, young children's own reports of PDT using the difference score method related crosssectionally to parent reports of behavior problems (Coldwell, Pike, & Dunn, 2008), mirroring earlier observational studies that also used the difference score method (e.g., Brody, Stoneman, & McCoy, 1992;Dunn, Stocker, & Plomin, 1990).…”
Section: Family-wide and Child-specific Effectsmentioning
confidence: 88%
“…Based on theory (Festinger, 1954; Suls et al, 2002) and previous research (e.g., Coldwell et al, 2008; McHale et al, 2000; Richmond et al, 2005), we hypothesized that parents' favoritism would be associated with young adults' well-being. Specifically, we hypothesized that favored treatment would be linked to fewer depressive symptoms, whereas less favored treatment would be associated with more depressive symptoms (H1).…”
Section: Discussionmentioning
confidence: 99%
“…For example, research suggests that within families, mothers and fathers may vary in their levels of differential treatment (McHale, Crouter, McGuire, & Updegraff, 1995). Despite these differences, to date, most studies have only examined maternal differential treatment (e.g., Coldwell et al, 2008; Pillemer et al, 2010), or maternal and paternal differential treatment in separate models (e.g., Feinberg & Hetherington, 2001; McHale et al, 2000). Of the few studies that have examined maternal and paternal treatment concurrently, some (Brody, Stoneman, & McCoy, 1992; Tamrouti-Makkink et al, 2004) have found that differential treatment from fathers accounted for more variance in adjustment outcomes of children than that from mothers.…”
Section: The Role Of Sibling Gender Composition and Parent Gendermentioning
confidence: 99%